ЖОРСТКІСТЬ ПАРЕНХІМИ ПЕЧІНКИ ЩУРІВ ПРИ МОДЕЛЮВАННІ СТЕАТОЗУ АЛІМЕНТАРНОГО ГЕНЕЗУ ТА ЙОГО КОРЕКЦІЇ - В.І. Діденко; Ю.А. Гайдар; І.А. Кленіна; О.О. Галінський; І.С. Коненко; А.І. Руденко; О.І. Грабовська (Проблеми екології та медицини)
Over the past decades, there has been an increase in the incidence of chronic diseases of the liver. Diseases with characteristic changes in the liver, which are combined with metabolic syndrome and insulin resistance, are found in 80% of cases. Therefore, the timely manifestation and appropriate treatment of this pathology is very important today. Recently, there has been an increasing interest towards less invasive and non-invasive methods for the study of liver pathologies. One of the approaches to the verification of steatosis is the method of evaluating the controlled parameter of ultrasound suppression, the method is based on the properties of ultrasonic signals "to fade" in the tissues containing fat droplets. The aim of the work was to investigate the degree of parenchyma stiffness and the morphological pattern of the liver of rats in the conditions of the modeling of alimentary steatosis and after its correction with medications - coenzyme Q10 and methadoxine. The studies were performed on laboratory rats of the Wistar line. Simulation of steatosis in experimental animals was performed by alimentary disorders of the diet. In the course of morphological studies, it was found that in experimental rats development of steatosis with small-drop fat dystrophy, scattered throughout the particle plane and sinusoidal enlargement was observed, which was accompanied by increased stiffness of the liver parenchyma of rats. In animals, 30 days after steatosis modeling, rat liver parenchyma stiffness was less than that of the steatosis group and fat deposition in the hepatic cytoplasm of the hepatic lobe was observed. The use of Q10 and methadoxine in the simulation of alimentary steatosis in the liver of rats had a positive effect on the functional state of the liver, which was confirmed by morphological studies and shift wave elastography.